Novel surface-active monomers containing phosphate group: synthesis, properties and application - Borzenkov, M.; Galadjun, Y.; Mitina, N.; Boccaccini, Aldo. R.; Hevus, O. (Видавництво Львівської політехніки, 2013)
Abstract – Polietilenglicol-containing maleate interaction with phosphorus (V) oxochloryde has led to formation of a novel surface-active monomer with the terminal phosphate group. The polymerization ability of the synthesized monomer was studied in the processes of binary and tertiary copolymerization with peroxide-containing monomer 5-Tertbutylperoxy- 5-methyl-2-hexene-3-yne (VEP) and N-vinyl pyrrolidone to form a surface-active copolymers. The possibility of using these copolymers as surface-active macroinitiators of emulsion polymerization of styrene and composites, to create polymeric substrates for tissue engineering was shown.
Keywords: surface activity; surface-active monomers; phosphates; organic surface-active copolymers